Mesoporous carbon as a carrier for celecoxib: The improved inhibition effect on MDA-MB-231 cells migration and invasion - Wenquan Zhu; Qinfu Zhao; Xin Zheng; Zhiwen Zhang; Tongying Jiang; Yaping Li; Siling Wang (Elsevier, 2014)
In the current study, mesoporous carbon (MC) with pore volume (1.53 cm3/g) and pore size (9.74 nm) was successfully prepared as a carrier for celecoxib (CEL). Celecoxib was loaded into the pore channels of MC using three different methods: solvent evaporation method, absorption method and physical mixing method. Solid-state characterization methods, such as SEM, TEM, BET, DSC and XRD were used to systematically investigate the process of the drug loading system. Dissolution tests were performed to examine the effects of MC on the release of CEL. Furthermore, the cytotoxicity, wound healing, migration and invasion experiments were carried out to measure the contribution of MC to the anti-tumor metastasis ability of celecoxib on MDA-MB-231 cells. The results showed that CEL could be kept in a non-crystalline state when they were incorporated into the MC using the solvent evaporation method or absorption method. The dissolution rate of CEL released from MCS (Mesoporous carbon - Celecoxib - Solvent evaporation method) and MCA (Mesoporous carbon - Celecoxib - Absorption evaporation method) was all significantly higher than that of pure CEL. The cumulative release for MCS within the 5 min was up to 51.86%. MCS enhanced the inhibitory effect of CEL on the migration and invasion of MDA-MB-231 cells.